Konsep Pahala Ilahi dalam Tasawuf Sunni: Analisis Pemikiran Imam Al-Nawawi tentang Ikhlas, Amal, dan Karunia Tuhan - Ali Yusuf Muzaki; Zakaria Zakaria; Ridwan Ridwan; Agus Salim; M. Farid Zaini (Jurnal Shaf, 2026)
The concept of divine reward in the Sunni Sufi tradition intersects with issues of sincerity (ikhlash), the nature of deeds, and divine grace. Imam al-Nawawi (631-676 AH), as a central figure in Shafi'i-Ash'ari scholarship, holds a distinctive view on the relationship between sincerity, deeds, and divine reward. Previous studies have focused on reward within Mutazilah-Ashariyyah theological discourse and in interdisciplinary hadith approaches as offered by Azhary et al. in Nabawi Journal (2024), leaving the Sufi dimension of al-Nawawi's thought underexplored. This study asks: (1) how does al-Nawawi conceptualize divine reward from a Sunni Sufi perspective; (2) how do sincerity, deeds, and divine grace interrelate in his thought. A library research method with descriptive-analytical and comparative approaches is employed. Results indicate that al-Nawawi views sincerity as the primary condition for the acceptance of deeds, while divine reward remains entirely a grace that cannot be demanded. This affirms the unity of shari'ah, Sufism, and Ash'ari theology in al-Nawawi's thought.